The Interface Between Wheat and the Wheat Curl Mite, Aceria tosichella, the Primary Vector of Globally Important Viral Diseases - Skoracka, Anna; Rector, Brian G.; Hein, Gary L. (Frontiers in Plant Science, 2018)
Wheat production and sustainability are steadily threatened by pests and pathogens, in both wealthy and developing countries, and their impact is increasing due to global climatic changes. This review is focused on the wheat curl mite (WCM), Aceria tosichella, and its relationship with wheat. WCM is a major pest of wheat and other cereals and a vector of at least four damaging plant viruses (WSMV, HPWMoV, TriMV, BSMV). The WCM-virus pathosystem causes considerable yield losses worldwide, and its severity increases significantly when mixed-virus infections occur. Chemical control strategies are largely ineffective because WCM occupies secluded niches on the plant, e.g. leaf sheaths or curled leaves in the whorl. The challenge of effectively managing this pest-virus complex is exacerbated by the existence of divergent WCM lineages that differ in host-colonization and virus-transmission abilities. We highlight research progress in mite ecology and virus epidemiology that affect management and development of cereal cultivars with WCM- and virus-resistance genes. We also address the challenge of avoiding both agronomically deleterious side effects and selection for field populations of WCM that can overcome these resistance genes. This report integrates the current state of knowledge of WCM-virus-plant interactions and addresses knowledge gaps regarding the mechanisms driving WCM infestation, viral epidemics and plant responses. We discuss the potential application of molecular methods (e.g. transcriptomics, epigenetics, whole-genome sequencing) to understand the chemical and cellular interface between the wheat plant and WCM-virus complexes.